Role of TRPM7 kinase in cancer. (June 2021) - Meng, Selena; Alanazi, Rahmah; Ji, Delphine; Bandura, Julia; Luo, Zheng-Wei; Fleig, Andrea; Feng, Zhong-Ping; Sun, Hong-Shuo
Highlights: The role of the TRPM7 kinase in cancer is distinct from activity of the ion channel. The TRPM7 kinase is involved in cell migration but not proliferation of certain cancers. The TRPM7 kinase phosphorylates a variety of substrates to promote tumorigenesis. Only one potent TRPM7 kinase inhibitor currently exists. Abstract: Cancer is the second leading cause of death worldwide and accounted for an estimated 9.6 million deaths, or 1 in 6 deaths, in 2018. Despite recent advances in cancer prevention, diagnosis, and treatment strategies, the burden of this disease continues to grow with each year, with dire physical, emotional, and economic consequences for all levels of society. Classic characteristics of cancer include rapid, uncontrolled cell proliferation and spread of cancerous cells to other parts of the body, a process known as metastasis. Transient receptor potential melastatin 7 (TRPM7), a Ca 2+ - and Mg 2+ -permeable nonselective divalent cation channel defined by the atypical presence of an α-kinase within its C-terminal domain, has been implicated, due to its modulation of Ca 2+ and Mg 2+ influx, in a wide variety of physiological and pathological processes, including cancer. TRPM7 is overexpressed in several cancer types and has been shown to variably increase cellular proliferation, migration, and invasion of tumour cells. However, the relative contribution of TRPM7 kinase domain activity to cancer as opposed to ion flux through its channel pore remains an area of active discovery. In this review, we describe the specific role of the TRPM7 kinase domain in cancer processes as well as mechanisms of regulation and inhibition of the kinase domain.